Delayed onset of severe immune thrombocytopenia associated with COVID-19 pneumonia. (2021) - Sato, Shintaro; Kurachi, Moegi; Ohta, Hiroki; Nakamura, Tomohiko; Oba, Tomohiro; Kawabe, Rie; Yamakawa, Hideaki; Amano, Masako; Matsushima, Hidekazu
Abstract: A 72-year-old Japanese man was admitted to our hospital for treatment of severe COVID-19 pneumonia and was started on favipiravir, heparin calcium, and methylprednisolone pulse therapy. He recovered from respiratory failure about one month later. However, he soon developed purpura in his lower limbs and thrombocytopenia, and immune thrombocytopenia was subsequently diagnosed. Although immune thrombocytopenia is one of the early complications of COVID-19, the use of corticosteroids for COVID-19 is thought to be a factor in the late onset of immune thrombocytopenia. In cases of severe COVID-19 for which corticosteroids were used for treatment, autoimmune diseases such as immune thrombocytopenia may manifest themselves late in the disease course.